The Relationship of Psychological Skill with Stress Recovery on Wrestling Athletes in Indonesia - Dewi Atiya Dewi; Berliana; Komarudin (Gladi : Jurnal Ilmu Keolahragaan, 2022)
This study aims to determine the relationship between psychological skills (X ), and stress recovery in wrestling athletes (Y). This research is a correlation research with the aim of connecting the independent variable and the dependent variable. The sample in this study were 104 wrestling athletes who participated in PON XXI 2021 Papua. Data collection techniques used the Test of Performances Strategies (TOPS) questionnaire and Recovery-Stress Questionnaire for athletes (RESTQ-Sport 76). sig 0.777, statistical test of product moment correlation with a significant level of 5%. The results of a simple linear regression test between psychological skills (X ) and stress recovery (Y) 0.000 < 0.05, it can be said that there is a significant relationship between psychological skills and stress recovery for wrestling athletes in Indonesia. Meanwhile, the degree of relationship between psychological skills and recovery The stress of wrestling athletes in Indonesia can be seen in column R which shows the number 0.824, with the R value when referring to the guidelines for the degree of relationship that is in perfect correlation. The magnitude of the contribution of psychological skills to the stress recovery of wrestling athletes in Indonesia is in the R Square column which shows a value of 0.679 or a percentage of 67.9%. The results of the study indicate that the importance of the psychological ability of athletes to stress recovery in athletes when competing, then it is hoped that there will be research that will examine the psychology of wrestling athletes in other ways